Privatization and deregulation of transport - Bradshaw, William; Lawton Smith, Helen; Hertford College (University of Oxford). (Basingstoke : Macmillan, 2000)
This book is based on a seminar held at Oxford University in September 1997. The seminar sought to address somewhat contradictory situation of a government on the left, inheriting a transport industry largely privatized and deregulated, but unwilling to commit itself to the expense of renationalization or to finding the large sums of money needed for investment in public infrastructure and facilities.
Includes index.
osc 01/09/16
Loans
Keywords: Deregulation; Transportation and state; Privatization